2018
DOI: 10.1080/08830185.2018.1465943
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory T-cell dynamics with abatacept treatment in rheumatoid arthritis

Abstract: The progressive damage in rheumatoid arthritis (RA) has been linked to an increase in inflammatory Th1/Th17 cells and a decrease in number or function of immunomodulatory regulatory T cells (Tregs). Many therapies that are effective in RA are shown to affect Th1/Th17 cells and/or Tregs. One such therapy, abatacept, utilizes a physiologic immunomodulatory molecule called cytotoxic lymphocyte antigen-4 (CTLA-4) which causes contact-dependent inhibition of inflammatory T-cell activation. Recent advances in CTLA-4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 56 publications
2
16
0
Order By: Relevance
“…Furthermore, the development of GCs, autoantibodies, and autoimmune disease was not dependent upon prolonged circulation of CTLA4-Ig, which lasted 10-14 d. When young BXD2 mice were administered Ad-CTLA4-Ig at 2 mo of age, before significant autoantibodies and autoimmune disease was apparent, they remained autoantibody and disease free for up to 8 mo of age. These results are consistent with several reports that CTLA4-Ig promotes the function of Treg cells in patients with RA (148,149). It also has been reported that CTLA4-Ig may enhance IL-10 production by Treg cells and 1,25(OH)2D3 promotes the efficacy of CD28 costimulation blockade by abatacept (150).…”
Section: Therapeutic Directionssupporting
confidence: 92%
“…Furthermore, the development of GCs, autoantibodies, and autoimmune disease was not dependent upon prolonged circulation of CTLA4-Ig, which lasted 10-14 d. When young BXD2 mice were administered Ad-CTLA4-Ig at 2 mo of age, before significant autoantibodies and autoimmune disease was apparent, they remained autoantibody and disease free for up to 8 mo of age. These results are consistent with several reports that CTLA4-Ig promotes the function of Treg cells in patients with RA (148,149). It also has been reported that CTLA4-Ig may enhance IL-10 production by Treg cells and 1,25(OH)2D3 promotes the efficacy of CD28 costimulation blockade by abatacept (150).…”
Section: Therapeutic Directionssupporting
confidence: 92%
“…All 3 cases occurred early in the disease (11–46 days after randomization), while the 1 case in the placebo group occurred 56 days after randomization. Inhibition of Treg cell function prior to reduction in the numbers and activity of pathogenic effector T cells in abatacept‐treated patients could account for early flares but could also lead to eventual reduction in disease activity in SSc , though data are needed to validate this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…Though our knowledge on the mechanisms of this fusion protein is still incomplete, current literature suggest that by interacting with B7 molecules on antigen-presenting cells, abatacept interferes with CD28-mediated T-cell signalling and activation [22]. Abatacept might also affect the activation of innate cells, such as monocytes and dendritic cells, and enhance Tregs, though data on the Treg function are limited and conflicting [23,24].…”
Section: @Erspublicationsmentioning
confidence: 99%